Power relations in the enactment of English language education policy for Chinese schools. Issue 5 (3rd September 2017) - Li, Minglin
ABSTRACT: The scale of English language education in China is astounding, but recent research has shown that the latest national English education policy for Chinese schools has not been implemented successfully due to various reasons. One reason given for the lack of success is the impracticability of the top-down policy itself excluding teachers' involvement and neglecting the contextual constraints. Building on the theoretical framework of multi-levelled actors in language planning and language policy, and drawing on some key concepts in relation to power in Critical Language Policy research, this paper explores how a national English language curriculum that emphasizes the international standards and norms in curriculum design has been enacted, ineffectively, by the key stakeholders through analysing the specific roles of three groups of key stakeholders involved in the English as a foreign language curriculum policy implementation.